2021
DOI: 10.3390/cells10061492
|View full text |Cite
|
Sign up to set email alerts
|

Therapy Development by Genome Editing of Hematopoietic Stem Cells

Abstract: Accessibility of hematopoietic stem cells (HSCs) for the manipulation and repopulation of the blood and immune systems has placed them at the forefront of cell and gene therapy development. Recent advances in genome-editing tools, in particular for clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein (Cas) and CRISPR/Cas-derived editing systems, have transformed the gene therapy landscape. Their versatility and the ability to edit genomic sequences and facilitate gene di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 266 publications
0
17
0
Order By: Relevance
“…The current results showed that PE3 successfully installed a therapeutic conversion of GGT > CCC and accordingly ameliorated the hematological and histopathological symptoms in a beta-thalassemia mouse model with the IVS-II-654 mutation. CRISPR/Cas9-derived gene modification, base editing, and prime editing have been utilized for precise gene therapies [ 16 , 18 , 19 , 20 ]. CRISPR/Cas9-mediated gene modification mainly involves homology-directed repair (HDR), NHEJ, microhomology-mediated end joining (MMEJ), and homology-mediated end joining (HMEJ) [ 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current results showed that PE3 successfully installed a therapeutic conversion of GGT > CCC and accordingly ameliorated the hematological and histopathological symptoms in a beta-thalassemia mouse model with the IVS-II-654 mutation. CRISPR/Cas9-derived gene modification, base editing, and prime editing have been utilized for precise gene therapies [ 16 , 18 , 19 , 20 ]. CRISPR/Cas9-mediated gene modification mainly involves homology-directed repair (HDR), NHEJ, microhomology-mediated end joining (MMEJ), and homology-mediated end joining (HMEJ) [ 18 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9-derived gene modification, base editing, and prime editing have been utilized for precise gene therapies [ 16 , 18 , 19 , 20 ]. CRISPR/Cas9-mediated gene modification mainly involves homology-directed repair (HDR), NHEJ, microhomology-mediated end joining (MMEJ), and homology-mediated end joining (HMEJ) [ 18 , 20 , 21 ]. We successfully corrected the IVS-II-654 (C > T) mutation in the same mouse model using a Cas9-mediated HMEJ method, and are planning to publish the results elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…[95][96][97] Analogous strategies will likely follow for the lymphoid regulator IL7R 86,98 and the other 170 single gene mutations known to impair human hematopoiesis. 99 Due to the life-long persistence of transplanted HSCs, these strategies are potential single-treatment, permanent cures. We expect that this is just the beginning of life-saving CRISPR-edited HSC therapies.…”
Section: Current Clinical Applications Of Crispr-edited Hscsmentioning
confidence: 99%
“…A few pre‐clinical studies have also demonstrated proof of concept CRISPR‐based therapies to treat severe combined immunodeficiency (SCID) and chronic granulomatous disease (CGD) by targeting IL2RG and CYBB, respectively, in HSCs 95–97 . Analogous strategies will likely follow for the lymphoid regulator IL7R 86,98 and the other 170 single gene mutations known to impair human hematopoiesis 99 . Due to the life‐long persistence of transplanted HSCs, these strategies are potential single‐treatment, permanent cures.…”
Section: Current Clinical Applications Of Crispr‐edited Hscsmentioning
confidence: 99%
“…Despite the fact that other gene editing techniques exist, CRISPR/Cas9 is the most reliable and efficient proven method for gene rectification. [100][101][102][103] Genome engineering employing CRISPR/Cas has proven to be a strong method for quickly and accurately changing specific genomic sequences. The rise of innovative haematopoiesis research tools to examine the complexity of hematopoietic stem cell (HSC) biology has been fuelled by considerable advancements in CRISPR technology over the last five years.…”
Section: Crispr and Stem Cell Applicationsmentioning
confidence: 99%